Daya Antibakteri Air Perasan Buah Lemon (Citrus Limon (L.)Burm.F.) Terhadap Porphyromonas Gingivalis Dominan Periodontitis(In Vitro) - Berti, Pamela Lolita; , Drg. Soetomo Nawawi, DPH.Dent,Sp.Perio (K); , drg. Juwita Raditya Ningsih (2015)
Porphyromonas gingivalis is a pathogen bacteria that mostly found in periodontitis. Porphyromonas gingivalis produces some virulence factors such as gingipain, lipopolysaccharide (LPS), capsule and fimbriae, that can cause inflamation respons, induce proinflamatory cytokine, and damage periodontal ligaments. One of the treatment choices is antibiotic drugs that their properties also can be found in lemon. Lemon (Citrus limon (L.) Burm.f.) as a herbal medicine contains bioactived substances such as flavonoids, carotenoids, limonoids, tannin, and terpenoids. The aims of this study were to understand antibacterial activity of lemon juice, to understand antibacterial activity of lemon juice with certain concentration was equal to positive control chlorhexidine 0,2%, and to understand the developing of lemon juice concentration was followed by the developing of antibacterial activity against Porphyromonas gingivalis. This research was initiated by squeezing lemon to get lemon juice, and devided into 5 concentration afterwards which each concentration contains 60%, 70%, 80%, 90%, and 100% lemon juice per volume. Bacterial sensitivity test was done by dropping 30 μl each concentration of lemon juice using micropipette into plate contained 7 wells. The other 2 wells were filled by 30 μl clorhexidine 0.2% as positive control and 30 μl sterile aquadest as negative control. The result was read by measuring inhibiton zone of each well and analysed using one-way Anova with 95% confidence interval. Statistical result showed that lemon juice concentration (60%, 70%, 80%, 90%, and 100%) have antibacterial activity effects against Porphyromonas gingivalis (p=0,00)